State Property Management in the Republic of Kazakhstan - TAITORINA, Binur Adamovna; ZHARBOLOVA, Aigerim Zhaksylykovna; ZHAPAKOV, Sabyrzhan Malievich; SADIBEKOVA, Moldir; SADIBEKOVA, Moldir; KARASHEVA, Zhanar Toleubekovna; BURIBAYEV, Yermek Abiltayevich (Journal of Advanced Research in Law and Economics, 2016)
The relevance of the study is caused by necessity to provide legal analysis in the issues of increasing the efficiency of state property management, further development of national companies, national holdings and other new corporate government agencies engaged in public administration in the management of state property. Low efficiency of the administration of management process in this area; fragmentation of levels and branches of government, lack of clearly defined objectives of the state property; poor performance of state property management monitoring; lack of transparency in management procedures; together served as the basis for determining the direction of research, its nature, specificity, structure and methods of research. Thereby, this article determines the control mechanism by the state property; the study presents formation and the main trends of legislative regulation of state property as a control object; examines the legal characteristics of the phenomenon of state property and the nature and value of the state assets management as well; substantiates the systemic nature of state property management, consisting of two main elements –governmental and corporate structures activities in state property control; presents the analysis of legal framework in the area of administrative mechanisms of state property realization; investigates the issues of increasing efficiency of legal support of administrative relations dynamics which are the subject of the state assets. The major methods in the study of this problem are dialectical, logical, legal, social and legal, comparative legal and system-structural which allow to consider the problems of state property management comprehensively. The study formulated the following conclusions and recommendations: the main parameters of a legal mechanism to ensure control of state property; the main trends in the evolution of legislative support of state property management are defined; the controlling system of state authorities in state property management is defined, set it functioning modern trends, the modern trends of its functioning are defined. The role of local authorities in the mechanism of state property management is reviewed. The corporate state property management system is revealed, its subjects are defined, their organizational and legal forms of activity are investigated, the principles of their activity on state property management are summarized. The authorities of administration activities in state property management are systematized, the constitutional foundations of their interaction are determined. The problems of legal ensuring the effective of state assets management are revealed, the recommendations for law-making activities in this area are given. The identified as a result of the study main parameters of legal control mechanism in ensuring public property management address issues of legal support in providing effective management in the legislative process in this area.
Keywords: public administration; state property; authorities